Pemaknaan Jihad Dalam Al-Qur'an dan Hadis Dengan Pendekatan Historis-Sosiologis (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2020)
This article intends to decipher the meaning of jihad in the Koran and the Hadith by using a historical-sociological approach, with the consideration that the growth and development of Islam both during the Mecca and Medina periods cannot be separated from the command of jihad which is explicitly stated explicitly in the verses of the Qur'an and the traditions of the Prophet. Jihad in both sources of Islamic teachings means to be serious in upholding the truth and preventing munkar. However, the meaning of jihad is often misunderstood by both Muslims and non-Muslims internally by giving narrow meanings to jihad which only means physical struggle and even vulnerable to acts of violence. Data collection techniques using documentation techniques to be analyzed descriptively-critically